You'll miss me when I'm gone - Solomon, Rachel Lynn (Simon Pulse, 2018)
Eighteen-year-old twins Adina, a viola prodigy, and Tovah, a future surgeon, find their relationship tested when they learn that one of them will develop Huntington's, the degenerative disease ravaging their mother.